PERANCANGAN SISTEM INFORMASI ABSENSI BERBASIS WEB STUDI KASUS DI KANTOR PUSKOD BARANAHAN KEMHAN - Muhamad Rizqi; Rayyan Nurjihan; Iwan Giri Waluyo (Shofanah Media Berkah, 2023)
The web-based employee attendance application as an identification tool is an efficient and practical solution for the Baranahan Kemhan Puskod Office in managing employee attendance recap. Making an employee attendance system is done by means of system analysis, system design, system implementation, and testing. This system is created using the programming language PHP and MySQL for database management. As a result, a web-based employee attendance application was created to accurately identify employees and manage attendance data efficiently.